European Respiratory Society International Congress 2018: Allied Respiratory Professionals' report of highlighted sessions. Issue 1 (1st February 2019) - Rutter, Matthew; Camillo, Carlos Augusto; Coss, Peter; Sajnic, Andreja; McGowan, Aisling; Langer, Daniel; De Brandt, Jana; Osadnik, Christian
This article provides an overview of outstanding sessions that were supported by Assembly 9 during the recent European Respiratory Society International Congress in Paris, France. Session content was mainly targeted at allied health professionals such as respiratory physiologists, respiratory physiotherapists and respiratory nurses. Recent developments and novel findings related to pulmonary function testing, respiratory muscle function assessments and treatment, and multidimensional and multidisciplinary approaches to the assessment and management of dyspnoea were the focus of these sessions and are summarised here. An overview of outstanding sessions that were supported by Assembly 9 during the 2018 European Respiratory Society International Congress in Paris, France. http://ow.ly/OO8P30mXs3q